Aphasia in an Internet age: wider perspectives on digital inclusion. Issue 2 (3rd March 2016) - Menger, Fiona; Morris, Julie; Salis, Christos
Abstract : Background : Aphasia is likely to impact adversely on the ability to use the Internet successfully, as linguistic skills are important for many aspects of Internet use. Despite this, there exists limited evidence on how best to support people with aphasia to benefit from the Internet. Whilst linguistic impairments in aphasia will have an impact on Internet use, there are other important factors such as other cognitive or physical impairments. There are also differences in digital skills between social groups in the UK, creating inequalities. People with aphasia and those who support them are likely to have varying levels of Internet use. These aspects are relevant in improving our understanding of factors relevant to supporting people with aphasia to use the Internet. Aims : The main aim is to discuss the key areas related to supporting people with aphasia to achieve equality of access to and use of the Internet. This paper focuses on three questions related to Internet use: (1) What do we know about access and use of the Internet by populations who share characteristics with people with aphasia and may experience similar disabilities?, (2) Based on that knowledge, what types of difficulties with Internet use might be predicted for people with aphasia? and (3) How has Internet use or support with Internet skills been studied in relation to people with aphasia. If not directly studied, what does relevant related work tell us? Main Contribution : This paper discusses factors that might act as barriers or facilitators to Internet use by people with aphasia, viewed from within the conceptual frameworks of the International Classification of Disability and Functioning and the Communications Consumer Panel Framework on Digital Participation. It considers the relevant literature on digital exclusion in the wider population and on aphasia and technology, in order to present a wide perspective on the range of issues involved in mitigating digital exclusion. Conclusions : The interrelationships between the complex demands imposed by aphasia and factors thought to contribute to digital exclusion are complex and multifactorial. The literature directly relating to aphasia and technology and from wider evidence on digital exclusion all contribute to understanding of key barriers and facilitators to Internet use. Consideration of these wider factors and of the contributions from a range of disciplines, historically not involved in aphasia rehabilitation, is helpful in understanding the needs of people with aphasia in a digital age and to develop future interventions.